Implikasi Materi Ajar Qur’an Hadis Kelas XII Tentang Kelestarian Lingkungan Terhadap Perilaku Siswa Dalam Menjaga Kebersihan Lingkungan Sekolah (Studi di MA Fauzaniyyah Sukaresmi Garut) - Salamudin, Ceceng; Nurhalim, Nunur (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Maintaining environmental sustainability in schools is essential for students, yet it often presents challenges. This is evident in their daily behaviors, which frequently lack consistency in maintaining the cleanliness of the school environment. Consequently, it is crucial to reinforce the understanding of the Qur’an Hadith curriculum content for Grade XII, particularly concerning environmental preservation, to positively influence their everyday practices in upholding school cleanliness. The aim of this research is to describe the implications of the Qur’an Hadith curriculum content for Grade XII on environmental sustainability and its impact on students' behavior in maintaining cleanliness at Madrasah Aliyah Fauzaniyyah Sukaresmi Garut. The research methodology used is descriptive, with data collection techniques including observation, in-depth interviews, and document analysis. Data analysis was conducted through content analysis involving steps of data reduction, data presentation, and drawing conclusions. The research findings indicate a positive impact of the Grade XII Qur’an Hadith curriculum content on environmental sustainability on student behaviors in maintaining school cleanliness. This is evidenced by their increased awareness in disposing of waste properly, disciplined adherence to assigned cleaning schedules, and active campaigning for environmental awareness through various information media such as posters, stickers, and social media. Keywords: Qur’an Hadith Curriculum Content, Environmental Sustainability, Student Behavior